Modelling the climatic suitability of Chagas disease vectors on a global scale - Eberhard, Fanny E (eLife, 2020)
The Triatominae are vectors for Trypanosoma cruzi, the aetiological agent of the neglected tropical Chagas disease. Their distribution stretches across Latin America, with some species occurring outside of the Americas. In particular, the cosmopolitan vector, Triatoma rubrofasciata, has already been detected in many Asian and African countries. We applied an ensemble forecasting niche modelling approach to project the climatic suitability of 11 triatomine species under current climate conditions on a global scale. Our results revealed potential hotspots of triatomine species diversity in tropical and subtropical regions between 21°N and 24°S latitude. We also determined the climatic suitability of two temperate species (T. infestans, T. sordida) in Europe, western Australia and New Zealand. Triatoma rubrofasciata has been projected to find climatically suitable conditions in large parts of coastal areas throughout Latin America, Africa and Southeast Asia, emphasising the importance of an international vector surveillance program in these regions.